Analisis Pengaruh Pertumbuhan Penjualan dan Intensitas Modal terhadap Arus Kas Operasi: Studi Empiris Pada PT Sumber Alfaria Trijaya, Tbk Periode 2013–2024 - Meilila Citra; Rizqa Syahirah Yudyanto; Fanny Nur Qhotimah; Andrian Lukmana; Sonata Dewi Fortuna (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study analyzes the effect of sales growth and capital intensity on operating cash flow at PT Sumber Alfaria Trijaya, Tbk during the 2013–2024 period. The research problem raised is whether sales growth and capital intensity have a significant effect on the company's operating cash flow. The purpose of this study is to prove the relationship between these two independent variables and operating cash flow, thus providing a basis for managerial decision-making in Indonesian retail companies. The data used in this study are secondary data in the form of annual financial statements of PT Sumber Alfaria Trijaya, Tbk over the last eleven years. The method used is a quantitative approach with regression analysis, preceded by classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests to ensure the validity of the regression model. The results show that the residuals are normally distributed, the regression model is free from multicollinearity and heteroscedasticity, but there is positive autocorrelation in the residuals. Simultaneously, sales growth and capital intensity are proven to have a significant effect on the company's operating cash flow. These findings emphasize the importance of efficient management of sales growth and capital intensity in maintaining the stability of operating cash flow.